Object-based costing as an important tool for the economic analysis of sustainable development - Raulinajtys-Grzybek, Monika; Świderska, Gertruda Krystyna (Copernican Journal of Finance & Accounting, 2014)
The purpose of the article was to verify whether the object-based costing provides information about the costs and benefits that arise in the enterprise as a result of activities related to environmental and socio-economic factors. The constructive approach method was used for this purpose. The object-based costing model for healthcare providers has been designed and subjected to empirical verification. The critical analysis proved its usefulness for economic evaluation of sustainable development. The obtained results demonstrate its utility and applicability.